Epistemic Beliefs and Googling - Ståhl, Tore (Frontline Learning Research, 2019)
With the introduction of internet as a source of information, parents have observed youngsters’ tendency to prefer internet as a source, and almost a reluctance to learn in advance since “you can look it up when needed”. Questions arise, such as ‘Are these phenomena symptoms of changing beliefs about knowledge and learning? Is it at all possible to learn on a deeper level simply by looking up the basic facts, without memorizing them?’ Within an existing line of investigation, epistemic beliefs have been described as a set of dimensions. Although internet-based information and internet as a source of information have been acknowledged, studies so far have not explored how dealing with internet-based information relates to other epistemic beliefs dimensions. To capture how users view internet-based information per se but also in relation to other epistemic beliefs, I suggest three new dimensions, out of which the most crucial is labelled ‘Internet reliance’. Offloading memory using memory aids is not a new phenomenon but the ‘Internet reliance’ dimension indicates that especially internet-reliant users may be confusing external information with personal knowledge, with all the risks it may entail. Besides including beliefs about learning, this study also challenges earlier assumptions regarding uncorrelated dimensions.